2019
DOI: 10.1002/anie.201903765
|View full text |Cite
|
Sign up to set email alerts
|

A General and Air‐tolerant Strategy to Conjugated Polymers within Seconds under Palladium(I) Dimer Catalysis

Abstract: While current M0/MII based polymerization strategies largely focus on fine‐tuning the catalyst, reagents and conditions for each and every monomer, this report discloses a single method that allows access to a variety of different conjugated polymers within seconds at room temperature. Key to this privileged reactivity is an air‐ and moisture stable dinuclear PdI catalyst. The method is operationally simple, robust and tolerant to air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Literature reports of “transition‐metal‐free” cross‐coupling reactions inevitably must account for the high catalytic activity of Ni and Pd, which can promote reactions even at ppm levels . Inductively coupled plasma mass spectrometry (ICP‐MS) of crude reaction mixtures showed <2 ppm Ni and Pd.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reports of “transition‐metal‐free” cross‐coupling reactions inevitably must account for the high catalytic activity of Ni and Pd, which can promote reactions even at ppm levels . Inductively coupled plasma mass spectrometry (ICP‐MS) of crude reaction mixtures showed <2 ppm Ni and Pd.…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports of "transition-metal-free" cross-coupling reactions inevitably must account for the high catalytic activity of Ni and Pd, which can promote reactions even at ppm levels. [38][39][40][41][42] Inductively coupled plasma mass spectrometry (ICP-MS) of crude reaction mixtures showed < 2ppm Ni and Pd. Dark control reactions doped with ppm levels of nickel showed that > 50 ppm of nickel was required to achieve comparable reactivity to the photoinduced polymerization (Table S13).…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing this challenge, several recent papers have described a more 'user‐friendly' conjugated polymer synthesis, in which the polymerization is performed in air 18,19 . For example, Kanabara and coworkers reported an oxygen‐ and moisture‐tolerant synthesis of thienopyrroledione‐based conjugated polymers through a step‐growth direct arylation polycondensation, wherein refluxing conditions effectively deoxygenated the solution 18,20 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kanabara and coworkers reported an oxygen‐ and moisture‐tolerant synthesis of thienopyrroledione‐based conjugated polymers through a step‐growth direct arylation polycondensation, wherein refluxing conditions effectively deoxygenated the solution 18,20 . Most recently, Schoenebeck and coworkers demonstrated CP synthesis in air utilizing the high reactivity of a Pd(I) dimer‐based catalyst, which enabled high conversions to be reached before appreciable monomer deactivation via quenching 19 . One limitation of both studies is that control over the molar masses was not achieved, indicating non‐living processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation